Carbon Capture Storage dan Carbon Capture Utilization Storage (CCS/CCUS) sebagai Solusi Transisi Energi Fosil di Indonesia : CARBON CAPTURE STORAGE AND CARBON CAPTURE UTILIZATION AND STORAGE (CCS/CCUS) AS INDONESIA’S ENERGY TRANSITION - Putri, Arananda Dwi; Sasongko, Nugroho Adi; Yoesgiantoro, Donny (UNIB Press, 2024)
This study delves into Indonesia's pursuit of zero-emission clean energy by 2060, focusing on advanced light particle tracking technology and the transition to Clean Coal Technology (CCT) such as Carbon Capture Storage (CCS). Using a qualitative research approach with data from diverse sources, it discusses Indonesia's goals for reducing greenhouse gas emissions by 2030 per the National Determined Contribution (NDC) plan. Emphasizing strategies like Enhanced Oil Recovery (EOR), Enhanced Gas Recovery (EGR), and Carbon Capture Utilization and Storage (CCUS), the study highlights their role in emission reduction. It also analyzes global and Indonesian advancements in CCS/CCUS technologies, underlining their potential across sectors like oil and gas, power generation, and industries. The study advocates for regional cooperation and infrastructure development to promote CCS/CCUS adoption, stressing technological progress and international collaboration in Indonesia's clean energy journey and emission reduction efforts. The government's commitment to implementing CCS and CCUS is reflected in the Ministry of Energy and Mineral Resources Regulation No. 2 of 2023. Indonesia has a CO2 storage potential of 8.4 Gt CO2, and so far, there are 15 CCS and CCUS projects underway.